The Use of the Word “Kabura” (كبر) and Its Derivatives in the Qur’an: A Morpho-Semantic Study - Khusnul Khatimah Al Mudassir; Haeruddin; Zuhriah; Ilham Ramadhan (UIN Syekh Wasil Kediri, Indonesia, 2025)
This study examines the morpho-semantic mechanisms underlying the use of the word kabura (كبر) and its derivatives in the Qur’an. Variations in morphological patterns (wazn) are shown to significantly influence shifts in meaning across theological, ethical, and evaluative domains. The research employs a qualitative–descriptive, corpus-based approach using a complete retrieval technique to collect all Qur’anic instances of the root k-b-r. Data analysis integrates derivational morphology with Context Theory (Naẓariyyah al-Siyāq) to map evaluative polarity. The study identifies 161 occurrences distributed across 18 major derivational forms, consisting of 106 nominal (ism) forms and 55 verbal (fiʿl) forms. The findings demonstrate a systematic semantic pattern: (1) nominal forms such as al-kabīr and kibriyāʾ consistently express a positive evaluative pole denoting divine majesty; (2) verbal forms following the istafʿala pattern, such as istakbara, form a negative pole associated with human arrogance; and (3) several forms appear semantically neutral, with meanings determined entirely by context. These results offer pedagogical implications for Arabic language teaching, particularly in enhancing learners’ awareness of how morphological variation and contextual indicators jointly shape meaning in Qur’anic discourse, enabling more accurate interpretation and reducing semantic error. Penelitian ini mengkaji mekanisme morfo-semantik dalam penggunaan kata kabura (كبر) dan berbagai turunannya dalam Al-Qur’an. Variasi pola morfologis (wazn) terbukti memengaruhi pergeseran makna pada ranah teologis, etis, dan evaluatif. Penelitian menggunakan pendekatan kualitatif–deskriptif berbasis korpus dengan teknik penelusuran menyeluruh terhadap seluruh ayat yang memuat akar k-b-r. Analisis data mengintegrasikan morfologi derivatif dengan Teori Konteks (Naẓariyyah al-Siyāq) untuk memetakan polaritas evaluatif. Hasil penelitian mengidentifikasi 161 kemunculan yang terdistribusi dalam 18 bentuk derivatif utama, terdiri atas 106 bentuk nominal (ism) dan 55 bentuk verbal (fiʿl). Temuan menunjukkan pola semantis yang sistematis: (1) bentuk nominal seperti al-kabīr dan kibriyāʾ membangun kutub evaluatif positif yang merepresentasikan keagungan ilahi; (2) bentuk verbal berpola istafʿala seperti istakbara membentuk kutub negatif terkait kesombongan manusia; dan (3) beberapa bentuk bersifat netral dan maknanya ditentukan sepenuhnya oleh konteks. Temuan ini memberikan implikasi pedagogis bagi pembelajaran bahasa Arab, terutama dalam meningkatkan pemahaman peserta didik mengenai hubungan antara variasi morfologis dan penanda konteks dalam pemaknaan wacana Qur’ani sehingga mengurangi risiko kesalahan interpretasi.